Memahami Nilai Tukar Kripto dalam Ekonomi Digital: Pendekatan Investasi di Masa Kini - Rolando, Benediktus; Al-Amin, Al-Amin; Rahmat, Rahmat; Zuwardi, Zuwardi; Izmuddin, Iiz (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This research aims to understand the role of crypto exchange rates in the context of the digital economy and current investment approaches through the literature study method. The study utilized relevant literature to explore crypto market volatility and value, the influence of government regulation, blockchain technology, and investment diversification strategies. It was found that crypto exchange rates exhibit high volatility but remain attractive as an investment instrument due to the potential for significant returns. Government regulations and policies play a crucial role in determining the stability and adoption of cryptocurrencies. Blockchain technology provides security and transparency that increases investor confidence and opens up new opportunities in the digital finance sector. The COVID-19 pandemic has accelerated the adoption of crypto as an investment and transaction tool, emphasizing its role in the digital economy. Cryptocurrencies are now an important component in portfolio diversification strategies, helping investors adapt to modern market dynamics. Through this research, it is hoped that investors and policymakers can gain a deeper insight into crypto and its impact on investment in the digital era.